Economic Development and Resilience to Natural Catastrophes – Insurance Penetration and Institutions - Miriam Breckner; Florian Englmaier; Till Stowasser; Uwe Sunde (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper provides new evidence on the negative effect of natural catastrophes on economic development. The findings indicate that private insurance markets accommodate the negative effects of natural catastrophes in developed countries, whereas they do not seem to be effective in developing countries. This pattern explains the heterogenous effects of natural disasters on income that have been found in previous studies. The results suggest that insurance and a stable, well-institutionalized environment complement each other in mediating the negative disaster shock. The analysis is based on novel data on natural disasters and global insurance penetration rates and contributes to the ongoing debate about the implications of natural catastrophes for development.
Keywords: Q54; Q56; O13; 330